Sociology. - Giddens, Anthony; Sutton, Philip W. (2017)
'Sociology' provides an introduction to its field. The book is packed with student-friendly features such as boxes on 'thinking critically', 'using your sociological imagination', 'classic studies' and 'global society'.
Includes bibliographical references and index.
Keywords: Sociology; Society